PEMAANFAATAN MUSEUM RONGGOWARSITO SEBAGAI SUMBER PEMBELAJARAN SEJARAH SECARA LANGSUNG SISWA KELAS XI SMA NU 05 BRANGSONG KENDAL - Widiyastuti, Diah (Lembaran Ilmu Kependidikan, 2010)
Learning is a set of individual process which changes someones stimuli andenvironment into a number of information which can give ability to learner to do aperformance. In order to achieve an instructional goal effectively instructional aidsshould be used. One of the learning media supporting eleventh grade students ofSMANU 05 Brangsong Kendal was direct learning done in Ronggowarsito MuseumSemarang. The problem discussed in this study was how the direct learning of historywas applied in Ronggowarsito Museum for the eleventh grade students of SMA NU05 Brangsong Kendal. The second problem was how the students responded to theactivity. This study aims to know the application and the students responses to thedirect learning of history. The method used in this study was qualitative. The datawere collected through observation and interview. The result of the study showed thatby applying direct learning of history in the museum, the students motivationimproved significantly. Consequently, the students were confident in asking questionsand were active in doing assignments given by the teacher. The study concluded that toget rid of boredom in the history class the teacher should apply interesting techniquessuch as a visit to the Ronggowarsito Museum.Kata kunci: Museum Ronggowarsito, pembelajaran, sejarah, media pembelajaran